Penerapan Qris untuk Mendukung UMKM dalam Meningkatkan Efisiensi Transaksi Non-Tunai di Desa Singa - Riana Raharti; Trisnawati Lubis; Alfa Nadia Siregar; Juliana Nasution (Jurnal Pengabdian Masyarakat Waradin, 2026)
This study examines the implementation of QRIS (Quick Response Code Indonesian Standard) in supporting MSMEs in Singa Village, with a focus on the efficiency of non-cash transactions and strengthening the digital financial ecosystem. The method used is literature research with a qualitative approach. The results show that the implementation of QRIS in MSMEs in Singa Village has a positive impact in increasing transaction efficiency through payment speed, transparency of transaction recording, and ease of access to digital finance. QRIS facilitates MSMEs to access faster and more secure payment systems, while expanding market reach by facilitating transactions between consumers and merchants. In addition, the implementation of QRIS contributes to strengthening financial inclusion in the village community, providing opportunities for residents to be more involved in the digital economy. Thus, it can be concluded that QRIS not only increases the competitiveness of MSMEs but also plays a significant role in strengthening community finances in Singa Village, making it more inclusive and sustainable in the digital era. The implementation of this technology is expected to continue to encourage more equitable local economic growth.